2019
DOI: 10.12717/dr.2019.23.2.149
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Body Growth and Growth-Related Genes under Different Photoperiods in Olive Flounder, Paralichthys olivaceus

Abstract: This study examined the effects of different photoperiod conditions on olive flounder ( Paralichthys olivaceus ), a commercially important species in Korea. Daily variations in the expression of mRNA for the growth-related genes ary­lalkylamine N-acetyltransferase2 (AANAT2), preprosomatostatin1 (PSS1), and growth hormone (GH) were examined under a 12 h light:12 h dark photoperiod. All the genes were expressed at higher level during the dark period. Melatonin injections increased the expr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 39 publications
0
1
0
Order By: Relevance
“…It was also found that melatonin directly promoted the secretion of pituitary growth hormone (GH) in Oncorhynchus mykiss (Falcoń et al, 2003). Prolonged darkness induces melatonin secretion in Paralichthys olivaceus, which increases GH mRNA expression and thus promotes weight gain in this species (Kim et al, 2019). Therefore, an increase in melatonin within a certain range can promote fish growth.…”
Section: Introductionmentioning
confidence: 99%
“…It was also found that melatonin directly promoted the secretion of pituitary growth hormone (GH) in Oncorhynchus mykiss (Falcoń et al, 2003). Prolonged darkness induces melatonin secretion in Paralichthys olivaceus, which increases GH mRNA expression and thus promotes weight gain in this species (Kim et al, 2019). Therefore, an increase in melatonin within a certain range can promote fish growth.…”
Section: Introductionmentioning
confidence: 99%